Catch analysis in small mesh gill nets - Thomas, Saly N; Hridayanathan, C (Indian Journal of Fisheries, 2011)
Gill netting provide important advantages over many other fishing methods in a multispecies fishery. However, the simultaneous use of many small mesh sizes in the inshore waters needs monitoring. Landing data from small mesh gill nets of 30, 32, 34, 36, 38, 40, 48, 50 and 52 mm were collected for two years from canoes operating off Cochin. Seasonal usage of different mesh sizes, species composition, size composition and proportion of juveniles in the catch are discussed. A total of 38 species of fishes were caught pointing out the difficulty in managing the tropical multispecies fishery. Of the different mesh sizes used, 30 and 32 mm are to be used with restraint, as proportion of juveniles caught in these were substantial. This would render gill netting a more ecofriendly fishing method for the inshore waters.